2022
DOI: 10.1038/s41598-022-26000-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs within the Basal-like signature of Quadruple Negative Breast Cancer impact overall survival in African Americans

Abstract: We previously found that QNBC tumors are more frequent in African Americans compared to TNBC tumors. To characterize this subtype further, we sought to determine the miRNA–mRNA profile in QNBC patients based on race. Both miRNA and mRNA expression data were analyzed from TCGA and validated using datasets from the METABRIC, TCGA proteomic, and survival analysis by KMPLOT. miRNA–mRNAs which include FOXA1 and MYC (mir-17/20a targets); GATA3 and CCNG2 (mir-135b targets); CDKN2A, CDK6, and B7-H3 (mir-29c targets); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…MiRNA profiling of the TNBC tumor cells (and of several other types of tumors) can vary according to the populational group studied [20,26,[39][40][41][42][43][44]. Most of the data are, however, in the comparison of NHW to AA TNBC patients [26,40,[44][45][46][47]. In our previous study, we reported that ancestrally characterized AA patients, when compared to NHW, exhibited distinct patterns of copy number alterations (CNAs) and miRNA expression profiles in both their TNBC and non-TNBC tumor tissues [44].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA profiling of the TNBC tumor cells (and of several other types of tumors) can vary according to the populational group studied [20,26,[39][40][41][42][43][44]. Most of the data are, however, in the comparison of NHW to AA TNBC patients [26,40,[44][45][46][47]. In our previous study, we reported that ancestrally characterized AA patients, when compared to NHW, exhibited distinct patterns of copy number alterations (CNAs) and miRNA expression profiles in both their TNBC and non-TNBC tumor tissues [44].…”
Section: Introductionmentioning
confidence: 99%
“…Over 200 AAW-and CAW-INBC candidate biomarkers identified. Over the past decade, significant efforts have been made to identify prognostic biomarkers specific to AAW-TNBCs and CAW-TNBCs, resulting in the discovery of over 200 potential peptide biomarkers [67][68][69][70][71][72][73][74][75], and even encompassing metabolites and non-coding RNAs [76,77]. Despite this progress, these previous studies have faced considerable limitations, primarily due to the scarcity of AAW-TNBC cases, which hinders the determination of prognostic markers.…”
Section: Resultsmentioning
confidence: 99%